Union Territory of Delhi Draft Annual Plan 1982-83 Part I-Outline - Planning Commission (Planning Commission, 1981)
The Union Territory of Delhi has a total area of 1485/kms. This territory is having the highest density/Sq of population in the country, i.e. 1478 persons per Sq. Kms. This can mainly on attributed to its predominantly urban character as 84.3%/population is in urban areas. Accord- of in to 1901 census, the total population of Delhi is 61.86 lakhs showing an increase of 52.4% in a decade. This growth is more than double of all India and higher than anticipated earlier. This higher rate of growth is mainly on account of immigration as Delhi being the capital of the country has always been attracting large number of persons from all over India, particularly from neighboring states for a large variety of reasons mainly economic considerations. From the above, it would implement that this territory has following three prominent characteristics which have been kept in view while planning for Delhi.
Union Territory of Delhi
Planning Department Delhi Administration
Keywords: Elementary Education; Housing assistance to rural landless laborers; Environmental Improvement of slum areas; Minimum Needs Programme; provide piped water supply to rural villages; Rural Health; Rural Roads; Employment Situation; Agriculture & Allied Services; Production of food grains; fisheries Development